Understanding of Chinese Young Female Self-gift Consumer Behaviour under negative relationship problems circumstances - Wu, Tianyu (2016)
ABSTRACT Purpose This research aims to have a clear scope of young female self-gift consumer behaviour (SGCB) in China, particularly under the negative relationship problems circumstances. It also involves the cultural influence on the nature, motivations and following emotions of SGCB. Approach This research conducts 15 qualitative in-depth interviews, which focus on participants’ experiences and perceiving in particular situations. Snowball sampling technique is employed to recruit participants, and Interpretative Phenomenological Analysis (IPA) is used to analyse interviews data. Findings The findings first reveal the significant role of relationship Guanxi in Chinese culture, while young consumers also feel nervous and difficult to deal with different relationships in personal and working life. It then identifies these SGCB motivations under negative circumstances, which are To escape, To Revenge and to vent, and Deserved. Further, the types of mood-reparatory self-gifts are diversified and emotions states changes following SGCB are identified from feeling better to feeling guilty or regret. Moreover, the Chinese culture impacts on young female SGCB are discovered, which indicates that young consumers are more likely to engage in SGCB, which is a unique feature of SGCB in the context of China.